Effect of dispersants on the biodegradation of South Louisiana crude oil at 5 and 25 °C. (February 2016) - Zhuang, Mobing; Abulikemu, Gulizhaer; Campo, Pablo; Platten, William E.; Suidan, Makram T.; Venosa, Albert D.; Conmy, Robyn N.
Abstract: This article reports biodegradation rates for a commercial dispersant, JD-2000, South Louisiana crude oil (SLC) alone, and SLC dispersed with JD-2000 at 5 and 25 °C. Results from the biodegradation experiments revealed that Component X, a chemical marker for JD-2000, rapidly degraded at both temperatures. The application of JD-2000 decreased by half the overall biodegradation rate of aliphatic compounds at 25 °C. At 5 °C, a residual fraction consisting of iso - and n -alkanes (C29 –C35 ) persisted after 56 d. The combination of dispersant and higher temperature resulted in faster removal rates for 2- and 3-ring polycyclic aromatic hydrocarbons. When compared with Corexit 9500, our results suggest that the chemistry of the surfactant (or surfactants) in JD-2000 might have favored oil dissolution (substrate transport to the aqueous phase) as an uptake mechanism over adhesion, which requires direct contact of the biomass with the oil. Highlights: Biodegradation of light crude oil dispersed with JD-2000 by indigenous microorganisms. Comparison with tests conducted with Corexit 9500. The different roles of the two dispersants in microbial degradation. Biodegradability of surfactant ingredients in JD-2000 and Corexit 9500.